Feministische Perspektiven in der deutschsprachigen Medizinethik: eine Bestandsaufnahme und drei Thesen = Feminist perspectives in German-language medical ethics : a review and three hypotheses - Faissner, Mirjam; Hartmann, Kris Vera; Marcinski-Michel, Isabella; Müller, Regina; Weßel, Merle (Ethik in der Medizin, 2022)
Definition of the problem: Feminist approaches to medical ethics are well established in international discourses. By contrast, in the German-speaking medical ethical discourse, they still seem to be rather marginal. In this article, we analyze which feminist perspectives are prominent in German medical ethics and suggest new approaches. Arguments: We present our results from a systematized review of the literature, in which we identify existing feminist approaches within the German-speaking medical ethics discourse as well as research gaps. Based on the review, our preliminary research and discussions in the working group "Feminist perspectives in bio and medical ethics", we defend three hypotheses aimed at advancing the German feminist medical ethical discourse. We posit that (1) feminist medical ethics aim at (epistemic) justice, (2) feminist medical ethics are critical and context-sensitive, and (3) intersectional and postcolonial approaches within feminist medical ethics may contribute to epistemically just, critical, and context-sensitive medical ethics. Conclusion: We argue that feminist perspectives should be implemented as a fundamental perspective in medical ethics because they can bring together key dimensions such as epistemically just, critical, context-sensitive, intersectional, and postcolonial thinking.